Relationship Between Reaction Speed and Arm Muscle Explosion With Rowing Ability Of Junior Athletes Kutai Kartanegara - cahyono, didik; Risky Putra Cahyadi; Jupri, Jupri; Nurjamal, Nurjamal (International Journal of Education, Vocational and Social Science, 2023)
This researcher aims to find out whether there is a relationship between reaction speed and arm muscle explosive power with the 50-meter rowing ability of Junior PODSI athletes in Kutai Kartanegara Regency 2022. The type of research used is correlation research with two independent variables, namely reaction speed and arm muscle explosive power, and with one the dependent variable is the ability to paddle 50 meters. The population of this study was junior athletes from Podsi Kutai Kartanegara Regency with a total of 15 people. The sampling technique used is Total Sampling. The data collection technique used a reaction speed test with a ruler drop test, an arm muscle explosive power test with a tow-hand medicine ball put/chest pass test. Data analysis techniques were processed using the SPSS Version 21 program. Based on the results of data analysis, the following results were obtained: (1) There is a relationship between reaction speed and the ability to paddle 50 meters with a value of Recount = 0.682 > Rtable with a significance of 5% = 0.0514. (2) There is a relationship between the explosive power of the arm muscles and the ability to paddle 50 meters with a value of Recount = 0.711 > Rtable with a significant 5% = 0.514. (3) There is a relationship between reaction speed and arm muscle explosive power with the ability to paddle 50 meters with a value of Fount 15.405 > Ftable at a significant level of 5% and degrees of freedom 2:12 which is 3.885 and Recount (x1.x2) = 0.848 > R table (0.05)(15) = 0.514. Then the hypothesis states "There is a relationship between reaction speed and explosive power of the arm muscles with the 50-meter rowing ability of junior pods athletes in Kutai Kartanegara district.